2021
DOI: 10.1002/er.7121
|View full text |Cite
|
Sign up to set email alerts
|

A review of supercapacitors modeling, SoH, and SoE estimation methods: Issues and challenges

Abstract: Summary Supercapacitors (SCs), or ultracapacitors, due to their attractive features, such as, high power density, long life cycle, etc., have received much attention from the transportation sector. SCs can be used as an additional energy storage system (ESS) in combination with lithium‐ion batteries to enhance the performance of electric vehicles (EVs) in dynamic states, including acceleration and regenerative braking modes of operation. Online accurate estimation of SCs' state of health (SoH) and state of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 104 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Figure 2 shows a three-layer network. In real conditions, the hidden layer [ 10 , 19 , and 20 ] can have many fully connected neural networks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows a three-layer network. In real conditions, the hidden layer [ 10 , 19 , and 20 ] can have many fully connected neural networks.…”
Section: Methodsmentioning
confidence: 99%
“…However, the estimation error of this method is large, and it cannot be used for fast real-time estimation. The second category is model-based SOC estimation methods [ 10 ]. Due to the internal complexity of the battery, there is no ready-made model for use.…”
Section: Related Workmentioning
confidence: 99%
“…7 Laadial et al proposed a generalized model of supercapacitors with good robustness and high accuracy. 8 Allu et al established a generalized threedimensional model considering the charge transfer in the electrode-electrolyte system. 9 Bo et al proposed an artificial intelligence method to predict the thermal behavior of supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the estimating error of the SOC is less than 3% 7 . Laadial et al proposed a generalized model of supercapacitors with good robustness and high accuracy 8 . Allu et al established a generalized three‐dimensional model considering the charge transfer in the electrode‐electrolyte system 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation